Strangers at the gates : new immigrants in urban America - Waldinger, Roger David (University of California Press, 2001)
These essays look at U.S. immigration and the nexus between urban realities and immigrant destinies. They argue that immigration today is fundamentaly urban and that immigrants are flocking to places where low-skilled workers are in trouble.